2019
DOI: 10.1093/intqhc/mzz091
|View full text |Cite
|
Sign up to set email alerts
|

Trends in hospital standardized mortality ratios for stroke in Japan between 2012 and 2016: a retrospective observational study

Abstract: Objective Stroke is one of the leading causes of death and disability, and imposes a major healthcare burden. The aim of this study was to determine the characteristics of hospital standardized mortality ratios (HSMRs) for stroke in Japan for the year 2012–16 to describe the trend. Design Retrospective observational study. Setting Data from the Japanese admin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…An important caveat to note is that all patients that carry the diagnosis of acute ischemic stroke carry an increased risk of mortality compared to those without stroke on admission. 24 The mortality risk therefore may be intrinsically predicated with the stroke diagnosis as compared to the SARS-CoV-2 infection itself.…”
Section: A C C E P T E Dmentioning
confidence: 99%
“…An important caveat to note is that all patients that carry the diagnosis of acute ischemic stroke carry an increased risk of mortality compared to those without stroke on admission. 24 The mortality risk therefore may be intrinsically predicated with the stroke diagnosis as compared to the SARS-CoV-2 infection itself.…”
Section: A C C E P T E Dmentioning
confidence: 99%
“…Participation in the Medi-Target project was optional, and there were 182 participating hospitals in 2010, submitting about 500,000 claims data a year [8]. Details of the DPC database have been described elsewhere [12].…”
Section: Datamentioning
confidence: 99%
“…These data have been used in the design of health policies, disease management, and the analysis of healthcare processes and patient outcomes since its inception [9]. In Japan, several HSMR studies have been conducted [10][11][12][13] and the single-year HSMR model has already been created using administrative data for pneumonia [14]. Ian et al reported that diagnosis-specific HSMR is potentially a more fruitful method for monitoring mortality over time, which allows for the earlier identification of care deficiencies [4].…”
Section: Introductionmentioning
confidence: 99%
“…A frequently used measure of risk-adjusted mortality is the standardized mortality ratio (SMR) [ 6 12 ]. Using indirect standardization, the SMR relates the observed mortality rate of a hospital to its expected mortality rate.…”
Section: Introductionmentioning
confidence: 99%